Road map to success : developing a success model for women entrepreneurs – a concept paper / Sharifah Suzana Wan Shukran, Fauziah Noordin and Firdaus Abdullah - Wan Shukran, Sharifah Suzana; Noordin, Fauziah; Abdullah, Firdaus (2012)
Women entrepreneur are debatably is an important actors in our economy. The entrepreneurial landscape and the growing importance of the women entrepreneur have observed a massive change. Although the numbers are still small as compared to men, the involvement however is still increasing and encouraging. Based on the concept of Entrepreneurial Orientation (EO), Market Orientation (MO) and Social Networking, this study aims to develop a success model which can be guidance for women to be a successful entrepreneur. EO, MO and Social Networking will be tested to examine their influence on the performance of women entrepreneurs with the existence of Government Initiatives as the moderating factors.